Prevalence of H. Pylori in gastric biopsy specimens with the histopathological assessment of gastric mucosa between 2015 and 2023: A cross-sectional study - Mohammed N Hilmi; Batool Mahdi; Hujaz Alqirbi (Babcock University Medical Journal, 2025)
Background: Helicobacter pylori (H. pylori) is a gram-negative aerobic bacterium that primarily inhabits the stomach mucosa and is the leading cause of gastric atrophy and cancer. This study will detect the prevalence of H pylori infection with its combined effect on histopathological changes between 2015 and 2023.